Socio-Health Profile of Residents in Bhaktapur in Elder Care Homes - Raut, Rekha (Educational Journal, 2024)
Nepal is facing a low fertility rate, with a sharp increase in the senior citizens group. This has been in combination with the loss of support system of family, inadequate provisions of social security, and the result has been the strengthening of the demand for institutional care. In line with this, the current study reviews the socioeconomic and health characteristics of residents in five homes for the elderly in the Bhaktapur District. The goal is to create empirical evidence in evidence-based policymaking. 94 residents of five senior care facilities in Bhaktapur were surveyed as part of a census using a mixed-methods, cross-sectional design. Semi-structured questionnaires and interviews were used to gather information on sociodemographic traits, health status, and institutionalization reasons. To find significant correlations between variables, statistical analysis was used, including chi-square tests (p < 0.05) and descriptive statistics. Age and gender have a significant impact on the likelihood of living in a care facility, according to the results, with elderly women (59.57%) having a higher likelihood than men (40.43%). Among the primary reasons for institutionalization were financial instability and widowhood (74.4%). The illiteracy rate among the elderly population is high (69.15%), and women are more likely than men to be uneducated. According to the study, the two most common reasons for institutionalization were a lack of family care (26.6%) and spousal death (22.3%). Results from the chi-square test showed a significant relationship between gender and the reasons for residing in care facilities (p < 0.05). The researchers note that the research shows meaningful socioeconomic weaknesses and gender inequity between elderly care home residents in Nepal. The above results indicate why policy changes are necessary to facilitate health-care coverage, enhanced social security, and community-based health care. To improve the living conditions of elderly people and satisfy an active increase in the demand for sustainable elderly services in Nepal, interventions that will be gender-sensitive and measures to enhance financial stability should be entrenched in future practice.